P185 Global perception of normal life by healthcare professionals and IBD patients: mind the gap. (30th January 2023) - Van Oostrom, J; Anjie, S; Braad, M; Horrigan, J; Karimi, N; Adi, B; Ganesh, G; Yang, S K; Lasa, J; Broër, C; de Kruif, A; Olivera Sendra, P; et al.
Abstract: Background: For patients living with inflammatory bowel diseases (IBD), the ultimate treatment goal is "normal life". However, no patient-reported outcome measurement (PROM) exists to measure the level of life normality in IBD. We previously asked patients across the world (5 continents) to identify and rank-order items important to their "normal life". The top-25 ranked items are being used for subsequent PROM development. In this study, we aimed to compare the perception of healthcare professionals (HCP) and patients with IBD on normal life. Methods: IBD patients without an ostomy, pouch or significant comorbidities were interviewed in their mother tongue in 5 continents about "normal life" using a semi-structured interview guide. All items indicated as important were extracted from translated transcripts using directed content analysis (1) until saturation of items occurred. Categorisation was guided by the Wilson's & Cleary's Quality of Life model. (2) Second, in an online Delphi procedure, interviewed patients and HCP from each participating centre scored importance of each item on a 0-10 scale. Items scored 7 or higher by >75% were considered important to the respective group. Patient-ranked items were then presented to a patient focus group to clarify wording and merge similar items. Items merged in the patient focus group were merged similarly in HCP rankings. Third, HCP- and patient-rankings were compared. We compared top-25 items selected for PROM development and top-3 items per category. Results: 45 CD and 40 UC patients spread over 6 countries were interviewed (median age 36, 56% male, 68% employed, median disease duration 7 years [IQR 4-15]) (table 1). Saturation occurred after 33 CD and 36 UC interviews, yielding 156 unique items. In the Delphi procedure, 54 patients considered 31 items important for normal life with IBD of which 25 remained after focus group discussion. 34 HCP (12 IBD nurses, 16 IBD gastroenterologists, 6 colorectal surgeons) considered 72 items important. Top-25 rankings overlapped in 15 items between patients and HCP, being 5 of 12 physical, 1 of 4 activities, 2 of 3 social, 4 of 11 psychological items and 3 of 5 circumstances (table 2). Top-3 rankings per category overlapped in 2 physical, 1 activities, 2 social, 1 psychological items and 2 circumstances (table 3). Conclusion: We identified discrepancies in the perception of normal life with IBD between patients living with IBD and healthcare professionals (HCP). Of top-25 selected items for PROM development, 15 items overlapped between patients and HCP. Of top-3 items per category, the least overlap was seen in activities and psychological items. PROM development and international validation is ongoing.